Unpacking Appeals to Emotion: A Dual-Path Analysis - Yu, Shiyang (Informal Logic)

(untitled) (Informal Logic, 2026)
While appeals to emotion have traditionally been dismissed as fallacious, recent scholarship has highlighted their potential reasonableness. Yet the role of emotion in these appeals remains underexplored. To address this, under the constraint that appeals to emotion are conceived as premises-conclusion complexes, this paper develops an analytical framework featuring two distinct paths linking premises to the conclusion: a logical path and an emotional path. This framework shows that evaluating such appeals involves first assessing each path individually and then integrating them. Notably, different emotions may either reinforce one another or work in opposition. An agent commits the fallacy of appeal to emotion if they mistakenly perceive the conclusion to be justified when it is not. Drawing on this model, I offer two explanations for how strong emotions can lead to such a misperception. Finally, I examine how the emotional mode can influence the strength of an appeal to emotion, thereby illustrating the epistemological role of emotion in argumentation, as discussed by Howes and Hundleby (2018).